The Relationship between Pedagogical Competencies Educators and the Discipline of Students in Surau Tahfidz Al Jihad Jorong Salimpek Solok Regency - Warzukni Warzukni; Setiawati Setiawati (Universitas Negeri Padang, 2023)
This research is motivated by using the low subject of college students at Surau Tahfidz Al Jihad Jorong Salimpek. Allegedly because of the low pedagogic competence of educators. The aims of this study were to: (1) see the outline of the pedagogical competence of educators at Surau Tahfidz Al Jihad (2), see the outline of pupil subject at Surau Tahfidz Al Jihad and (3) discover the connection between the pedagogical competence of educators and the subject of students at Surau Tahfidz Al Jihad. This form of studies is descriptive correlational with a quantitative technique. The populace of this take a look at was fifty six humans and a sample of 28 humans with stratified random sampling technique. The data series method is a questionnaire and the tool used is a questionnaire. The information analysis approach used the proportion formulation and the spearman rho formula. The outcomes of this have a look at suggest that: 1) the pedagogical competence of educators at Surau Tahfidz Al Jihad is low, 2) the subject of students at Surau Tahfidz Al Jihad is low, and three) there's a great courting between the pedagogical competence of educators and the gaining knowledge of area of college students in Surau. Tahfidz Al Jihad. The thought of this research is that the Surau Tahfidz Al Jihad educators must be capable of improve their pedagogical competence. it's miles hoped that the manager will provide steering and development of the pedagogic competence of educators at Surau Tahfidz Al Jihad.